Usaha Pemanfaatan Limbah Budidaya Jamur Sebagai Bahan Baku Pembuatan Briket Untuk Energi di Kelompok Tani Jamur Sedyo Lestari - Denny Irawati; Naresvara Nircela Pradipta; Johanes Pramana Gentur Sutapa (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2017)
Mushroom farmer society Sedyo Lestari is located in the Argosari, Sedayu, Bantul. The high demand for mushrooms media (baglog) is a good business opportunities for this farmer society. But the process of baglog making requires a lot of energy in the form of firewood, especially for sterilization process of the baglog. On the other hand, the mushroom cultivation process itself remains the waste that can be used as fuel for the sterilization process. So far Sedyo Lestari farmer society members do not have the technology to used the mushroom cultivation waste as a fuel. Therefore, it is imperative to transfer knowledge of biomass briquetting technique. The method used in this activities are socialization, training, and mentoring by starting with the introduction of briquettes and briquetting technology. Subsequently made briquette-making machines followed by training briquette making. Mentoring and socialization were also made to all members of farmer society. Outcome of these activities was briquette-making machines that can be used by all members of the society as well as knowledge about the process of making briquettes. The benefit of using briquettes of mushroom cultivation media waste as fuel for subtitute the firewood can provide savings to the expenditures of farmers for buying firewood and solving the waste management problems for farmers.